Marketing control in international headquarters-subsidiary working relationships of industrial goods firms: the role of environmental context - Lukas Isenberg; Susanne Kreiter; Roland Helm; Christian Schmitz (Journal of Business Economics, 2022)
The use of marketing and sales control mechanisms is a core management activity for multinational corporations. However, research on controlling marketing and sales of international subsidiaries is scarce. In particular, the influence of a firm's economic and cultural environment on different control mechanisms has not been thoroughly examined yet. In attempting to fill these gaps, we build on Jaworski's (J Mark 52:23–39, 1988) framework from a subsidiary perspective on marketing and sales controls, applied by the headquarters of medium-sized industrial goods corporations. Through a rival model analysis, we determine the impact of the local environmental context on marketing and sales control types exerted by headquarters on subsidiaries located in foreign countries. To analyze the proposed model, this study deploys survey data of 184 subsidiaries from different industries and different European countries with headquarters in Switzerland. The results show that while environmental factors influence the marketing and sales control configurations, the effectiveness of marketing and sales controls is not contingent on environmental factors.
Keywords: M16; M31; 650; Marketing control; International marketing; Medium-sized corporations; Industrial goods; Sales management; Sales control